2017
DOI: 10.1177/1010428317725925
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of cholangiocarcinoma cell lines from patients in the endemic area of liver fluke infection in Thailand

Abstract: Cholangiocarcinoma is a rare type of cancer which is an increasingly discernible health threat. The disease is usually very difficult in diagnosis and various treatment modalities are typically not effective. Cholangiocarcinoma is a complex and very heterogeneous malignancy characterized by tumor location, different risk factors, molecular profiling, and prognosis. Cancer cell lines represent an important tool for investigation in various aspects of tumor biology and molecular therapeutics. We established two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…The human CCA cell lines were obtained from the Liver Fluke and Cholangiocarcinoma Research Center, Khon Kaen University (Thailand). The KKU‐452, KKU‐023, and KKU‐100 cell lines were established from primary cholangiocarcinomas derived from Thai patients chronically infested with Opisthorchis viverrini, and their genetic and biological features have been reported previously . KKU‐213 (previously named KKU‐M213) was established from the primary tumor of a Thai male with histologic type of human mixed (papillary and non‐papillary) carcinoma of the biliary tract, using the same protocols as described by Sripa et al The cell lines KKU‐100 and KKU‐213 were deposited for inclusion in the Japanese Collection of Research Bioresources (JCBR) Cell Bank, Osaka, Japan (http://cellbank.nibiohn.go.jp/~cellbank/en/search_res_det.cgi?ID=7096 and http://cellbank.nibiohn.go.jp/~cellbank/en/search_res_det.cgi?ID=7076).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human CCA cell lines were obtained from the Liver Fluke and Cholangiocarcinoma Research Center, Khon Kaen University (Thailand). The KKU‐452, KKU‐023, and KKU‐100 cell lines were established from primary cholangiocarcinomas derived from Thai patients chronically infested with Opisthorchis viverrini, and their genetic and biological features have been reported previously . KKU‐213 (previously named KKU‐M213) was established from the primary tumor of a Thai male with histologic type of human mixed (papillary and non‐papillary) carcinoma of the biliary tract, using the same protocols as described by Sripa et al The cell lines KKU‐100 and KKU‐213 were deposited for inclusion in the Japanese Collection of Research Bioresources (JCBR) Cell Bank, Osaka, Japan (http://cellbank.nibiohn.go.jp/~cellbank/en/search_res_det.cgi?ID=7096 and http://cellbank.nibiohn.go.jp/~cellbank/en/search_res_det.cgi?ID=7076).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the relevant toxic concentration of DHA, we exposed CCA cells to increasing concentrations of DHA and assayed the cell viability at 24, 48, and 72 h. For this experiment, we employed five CCA cell lines differing for their genomic asset (aneuploidity, oncogenes, and oncosuppressor genes mutations) and biological features (cell proliferation, cell migration, chemoresistance, in vivo tumorigenicity), as reported in the literature. 22,23,[28][29][30][31] The human immortalized cholangiocyte MMNK-1 cell line was included as bile duct epithelial benign counterpart of CCA. Data shown in Figure 1A indicated that 50 μM is the minimum DHA concentration eliciting the highest toxic effect in CCA cells.…”
Section: Dihydroartemisinin Induces Cell Death In Cholangiocarcinommentioning
confidence: 99%
“… 17 KKU-023 cells were established from pathologically proven bile duct cancer tissues of a patient who was resident in the northeast Thailand and from whom written informed consent was obtained. 18 The KKU-213 and KKU-100 cell lines were obtained from the Japanese Collection of Research Bioresources (JCRB) Cell Bank, Osaka, Japan. All of the cell lines were cultured in DMEM (Sigma-Aldrich Co., St Louis, MO, USA) supplemented with inactivated 10% FBS, 100 U/mL of penicillin–streptomycin, and NaHCO 3 in a humidified atmosphere containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Published CCA cell lines up to 2013 were reviewed by Zach et al 6 Several others have been established since then. [7][8][9][10][11] CCA cell lines used most frequently include iCCA cell lines RBE 12 and HuCC-T1, 13 pCCA cell lines KKU-100 14 and QBC939 15,16 and dCCA cell line TFK-1. 17 Key characteristics of these commonly used cell lines are portrayed in Table 2.…”
Section: Cell Linesmentioning
confidence: 99%